Waking the dead : the mindhunters - Brant, Kylie (New York : Berkley Sensation, 2009)
"Forensic anthropologist Caitlin Fleming knows bones. So she is the first one called when seven sets of skeletal remains are found dumped in a makeshift graveyard in the Oregon wilderness. The skeletons bear the same distinctive marks--and each is missing a skull... Cait needs outdoor guide Zach Sharper for one reason only--to help her find her way through the Willamette Forest as she pieces together clues. Despite the attraction that burns between them, Cait will let nothing shake her focus. Until the killer closes in to terminate the search--and the investigators on the verge of unmasking him..."--p. [4] of cover
Keywords: Forensic anthropologists -- Fiction; Serial murder investigation -- Fiction; Murder -- Fiction; Oregon -- Fiction